1981
DOI: 10.1111/j.1471-4159.1981.tb01698.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormality of Long‐Chain Fatty Acids in Erythrocyte Membrane Sphingomyelin from Patients with Adrenoleukodystrophy

Abstract: We have devised an analytical method for the determination of fatty acid composition of erythrocyte membrane sphingomyelin by chemical ionization mass spectrometry combined with capillary column gas-liquid chromatography. Fatty acid composition of erythrocyte membrane sphingomyelin from 8 patients with adrenoleukodystrophy (ALD) and 16 healthy controls were examined by this method. The ratio of hexacosanoic acid (C26:0) to docosanoic acid (C22:0) in erythrocyte membrane sphingomyelin from ALD patients was 2.6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…Fatty acid analysis of total erythrocyte lipids from patients with ALD and AMN showed an increase in very long chain fatty acids, confirming a prior report of elevations in the ratio of C26:0 to C22:0 in erythrocyte sphingomyelin (11). The magnitude of very long chain fatty acid accumulation in erythrocyte membranes of patients is less than that reported in brain, adrenal, nerve, cultured muscle, or plasma (6)(7)(8)12).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Fatty acid analysis of total erythrocyte lipids from patients with ALD and AMN showed an increase in very long chain fatty acids, confirming a prior report of elevations in the ratio of C26:0 to C22:0 in erythrocyte sphingomyelin (11). The magnitude of very long chain fatty acid accumulation in erythrocyte membranes of patients is less than that reported in brain, adrenal, nerve, cultured muscle, or plasma (6)(7)(8)12).…”
Section: Discussionmentioning
confidence: 53%
“…Recent studies have demonstrated that these tissues (6)(7)(8) and skin fibroblasts (9,10) cultured from patients having either disease accumulate long-chain saturated fatty acids, especially hexacosanoic acid (C26:0). Hexacosanoic acid has also been reported to be increased in erythrocyte sphingomyelin (11) ripheral nerve dysfunction, inadequate responses to cortrosyn (ACTH) stimulation, and pronounced elevations in plasma very long chain fatty acids as measured by gas-liquid chromatography (12).…”
Section: Introductionmentioning
confidence: 99%
“…Lipid composition of the livers (n = 3) and total plasma lipids (n = 5) were analyzed using gas chromatograph equipped with a glass capillary column. Three parameters of the VLCFAs in sphingomyelin from plasma, the ratio of hexacosanoic acid (C26:0) to docosanoic acid (C22:0), of pentacosanoic acid (C25:0) to C22:0, and of tetracosanoic acid (C24:0) to C22:0, were analyzed by chemical ionization mass spectrometry combined with capillary gas chromatography (25).…”
Section: Methodsmentioning
confidence: 99%
“…Peroxisomal disorders with defective/3-oxidation were screened by means of saturated very long chain fatty acid (VLCFA) analysis in serum sphingomyelin (Tsuji et al, 1981) with slight modification. Shortly, total fatty acids were extracted with chloroform-methanol using 0.5 ml of serum as starting material.…”
Section: Methodsmentioning
confidence: 99%